2009
DOI: 10.1002/stem.138
|View full text |Cite
|
Sign up to set email alerts
|

Implanted Adult Human Dental Pulp Stem Cells Induce Endogenous Axon Guidance

Abstract: The human central nervous system has limited capacity for regeneration. Stem cell-based therapies may overcome this through cellular mechanisms of neural replacement and/or through molecular mechanisms, whereby secreted factors induce change in the host tissue. To investigate these mechanisms, we used a readily accessible human cell population, dental pulp progenitor/stem cells (DPSCs) that can differentiate into functionally active neurons given the appropriate environmental cues. We hypothesized that implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 50 publications
5
120
0
2
Order By: Relevance
“…The most accessible mesenchymal cells collectively termed dental stem cells (DSCs) include dental pulp stem cells (DPSCs) [20], stem cells from exfoliated deciduous teeth [21,22], stem cells from the apical papilla (SCAP) [22], periodontal ligament stem cells (PDLSCs), and dental follicle progenitor cells (DFPSc) [24][25][26][27]. Implanted adult human dental pulp stem cells induce endogenous axon guidance [28]. Bone marrow MSCs (BMMSCs) have been described as colony-forming unit-fibroblasts (CFU-Fs).…”
Section: Regeneration and Repair Of Pulp And/or Dental Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The most accessible mesenchymal cells collectively termed dental stem cells (DSCs) include dental pulp stem cells (DPSCs) [20], stem cells from exfoliated deciduous teeth [21,22], stem cells from the apical papilla (SCAP) [22], periodontal ligament stem cells (PDLSCs), and dental follicle progenitor cells (DFPSc) [24][25][26][27]. Implanted adult human dental pulp stem cells induce endogenous axon guidance [28]. Bone marrow MSCs (BMMSCs) have been described as colony-forming unit-fibroblasts (CFU-Fs).…”
Section: Regeneration and Repair Of Pulp And/or Dental Structuresmentioning
confidence: 99%
“…Following transplantation, DPSCs are clonogenic cells, capable of self-renewal and multilineage differentiation. DPSCs are able to regenerate a dentin-pulp-like complex composed of mineralized matrix, with tubules lined by odontoblasts and an arrangement similar to the dentin-pulp complex found in normal teeth [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Pulp cells express bone markers such as bone sialoprotein, alkaline phosphatase, type I collagen and osteocalcin.…”
Section: Immature Dental Pulp Stem Cells (Idpsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial conduits that are effective in inducing axon regeneration across nerve gaps are composed of type I collagen, Integra NeuraGen (NG) nerve guides, and processed rat allografts, which have similar efficacy to AxoGen's Avance human decellularized allograft [134,330]. For 14-mm sciatic nerve gaps, the efficacy of isografts is superior to processed allograft, which is more effective than the NeuraGen grafts.…”
Section: Commercial Nerve Gap Conduitsmentioning
confidence: 99%
“…In this xenotransplantation, it was observed that avian trigeminal ganglion axons were guided toward implanted DPSCs via chemo-attraction between CXCL12, a stromal cell derived factor-1 that is secreted by implanted DPSCs, and its receptor CXCR4. 56 It is also well known that cultured DPSCs produce several neurotrophic factors, such as NGF and BDNF. These neurotrophic factors also serve to promote the survival of injured neurons.…”
Section: Neural Differentiation Of Dental Stem Cellsmentioning
confidence: 99%